Regional convergence of output per worker in China: A neoclassical interpretation - Erich Gundlach (Asian economic journal, 1997)
Regional output per worker has converged across Chinese provinces in 1979- 1989. The estimated rate of convergence is 2.2 percent. This rate of convergence can be explained by neoclassical growth model conditional on assumptions about factor mobility and production elasticities. My empirical results show that capital mobility has been high across Chinese provinces and that the production elasticity of human capital is about twice as high as the production elasticity of physical capital. With less interprovincial capital flows as the result of an expected increase in fiscal decentralization, the rate of convergence of regional output per worker is likely to decline.
Keywords: O41; 330; Arbeitsproduktivität; Interregionale Kapitalmobilität; Humankapital; China